Susceptibility of HIV-1 non-B subtypes and recombinant variants to Enfuvirtide - Holguín, Africa; Faudon, Jean Louis; Labernardière, Jean-Louis; Soriano, Vincent (Journal of clinical virology, 2007)
Data on susceptibility of HIV-1 non-B subtypes to Enfuvirtide (ENF) is rather limited. To determine if ENF could be active in vitro against HIV-1 non-B subtypes and how the gp41 genetic variability across variants may influence ENF susceptibility. Using PHENOSCRIPT ® Env, a recombinant envelope virus assay, ENF susceptibility was investigated in isolates from 19 drug-naive HIV-1-infected individuals harboring non-B subtypes. Using phylogenetic analyses of the gp41 gene, distinct HIV-1 subtypes were recognized: A (2), C (5), D (1), F (2), G (1), J (1), CRF02_AG (6) and CRF06 (1). Susceptibility to ENF and IC 50 values in vitro could be obtained in only 13 (68.4%) specimens, most likely due to the high genetic variability in HR1 and HR2 regions in the remaining cases. A wide range of IC 50 values with a median of 0.013 μg/ml was observed (range, 0.005–0.180 μg/ml). Natural polymorphisms, but not classical ENF resistance associated mutations within HR1 (residues 36–45) were identified in most non-B viruses. This study provides information about the baseline susceptibility to ENF in antiretroviral-naive subjects infected with different HIV-1 non-B subtypes. Susceptibility to ENF seems to be preserved despite high genetic variability in HR1 and HR2 regions.